2011
DOI: 10.1161/circgenetics.110.959221
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Double Deletion in LMNA Underlies Progressive Cardiac Conduction Disease, Atrial Arrhythmias, and Sudden Death

Abstract: Background— Cardiac conduction disease is a clinically and genetically heterogeneous disorder characterized by defects in electrical impulse generation and conduction and is associated with sudden cardiac death. Methods and Results— We studied a 4-generation family with autosomal dominant progressive cardiac conduction disease, including atrioventricular conduction block and sinus bradycardia, atrial arrhythmias, and sudden death. Genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…[21][22][23][24] In LMNA mutation carriers, non-missense mutations may result in more severe cardiac events such as malignant ventricular arrhythmias than from missense mutations. 21,23) Van Rijsingen et al evaluated risk factors for malignant ventricular arrhythmias in a multicenter cohort of 269 LMNA mutation carriers and found that non-missense mutations (indels, truncating mutations, or mutations affecting splicing) were an independent risk factor for malignant ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] In LMNA mutation carriers, non-missense mutations may result in more severe cardiac events such as malignant ventricular arrhythmias than from missense mutations. 21,23) Van Rijsingen et al evaluated risk factors for malignant ventricular arrhythmias in a multicenter cohort of 269 LMNA mutation carriers and found that non-missense mutations (indels, truncating mutations, or mutations affecting splicing) were an independent risk factor for malignant ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Since Bonne et al identified the first LMNA gene mutation in patients affected with autosomal dominant Emery-Dreifuss muscular dystrophy (EDMD), dilated cardiomyopathy (DCM) and conduction defects in 1999 [27], mutations in LMNA have subsequently been identified in individuals with isolated DCM, usually with a conduction defect [28]. Atrial or ventricular arrhythmias are often present and even precede the onset of DCM [28-33]. The heterogeneity of LMNA mutations was further established by the lack of clear genotype-phenotype correlations [26,34].…”
Section: Discussionmentioning
confidence: 99%
“…(Kochanek et al, 2011;Xu et al, 2010). Various types of heart diseases from the most common atrial fibrillation to the lethal sudden cardiac death have been associated with pacemaker defects (Marsman et al, 2011;Tsai et al, 2000). Recent studies have established a casual relationship between certain genetic defects and SAN abnormalities, though the genetic regulatory network is still not well understood (Aanhaanen et al, 2011;Puskaric et al, 2010).…”
mentioning
confidence: 99%